Rapid change in red cell blood group systems after the main Out of Africa of Homo sapiens - (:unkn) unknown (My University, 2025)
Despite the advances in paleogenomics, red cell blood group systems in ancient human populations remain scarcely known. Pioneer attempts showed that Neandertal and Denisova, two archaic hominid populations inhabiting Eurasia, expressed blood groups currently found in sub-Saharans and a rare "rhesus", part of which is found in Oceanians. Herein we fully pictured the blood group genetic diversity of 22 Homo sapiens and 14 Neandertals from Eurasia living between 120,000 and 20,000 years before present (yBP). From the ABO, Rh, Kell, Duffy, Kidd, MNS, Diego, H, secretor and Indian systems, we noted that the blood group allele diversity in the Neandertals remained unchanged since 120,000 yBP, while H. sapiens conquered Eurasia with blood group alleles presently exclusive to non-African populations, suggesting they may have differentiated right after the Out of Africa, between 70,000 and 45,000 yBP. Notably, Ust'Ishim possessed unknown alleles that may illustrate the lost genetic heritage of the early Eurasians. Lastly, Neandertals shared a unique Rh haplotype from which we updated the current RHD phylogeny. The contribution of this study is twofold. It enlightens the expansion patterns of H sapiens and recalls the anthropological effectiveness of genetic polymorphisms currently being surveyed for transfusion safety and pregnancy monitoring.
Keywords: African Research